Types of Indonesian Reduplication as The Translation Equivalence of English Lexicons - Rafi’ie, Muhammad; Pastika, I Wayan; Seri Malini, Ni Luh Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2018)
This journal entitled Types of IndonesianReduplication as the Translation Equivalence of English Lexiconsinvestigates the types of Indonesian reduplications and how the English lexicons are translated in Indonesian reduplications. The data of the research is drawn from an English narrative textbook “The Magic” (Byrne, 2012) and its translation version in Indonesian “The Magic” (Purwoko, 2012).   This study reveals three types of reduplications with their own distinctive forms and varieties on meaning implications, namely: full reduplication, partial reduplication, and imitative reduplication. Full reduplication consists of four sub-categories, namely: reduplication of simple words, reduplication of complex words, reduplication of bases within a complex word, and reduplication without corresponding single bases.   The results of the research show that meaning is structured and therefore, it can be analyzed and represented into another language. English inflectional and derivational morphology can correspond productively to Indonesian reduplications. A menu of affixes of both English and Indonesian are the corresponding features of the morphological processes and the meaning components involvedin the translation equivalence analysis. The translation equivalence is then established by textual equivalence and formal correspondence or by contextual relations of the contextual meaning and relatable situational features of grammatical functions of the English lexicons into Indonesian reduplications.